EU Integration and the Change of Spatial Organization in Turkey - Gülden Erkut; Mete Başar Baypinar (European Regional Science Association (ERSA), 2003)
After 1980, economic agenda changed and international trade and integration to global and regional systems gained more importance in Turkey, like in many countries. As a candidate of the EU Turkey as well has experienced a change in the spatial organization. It has been shown by many other studies that integration process leads to a change in the industrial structure and spatial organization. The effect of the removal or lowering of trade barriers and its effects on the industrial location has been widely investigated in the New Economic Geography literature. These effects are of great importance for some essential grounds of European Integration, such as a balanced regional development and decreasing inequalities among regions to increase overall competitiveness, since they may cause an increase in the regional disparities and conflict with main targets of integration. This paper analyses the change of spatial organization in Turkey through the integration process to the EU by using location quotient, dissimilarity index and some other indicators and tries to show whether if spatial organization changed in favour of existing centres or if new centres have emerged.
Keywords: 330